Reforming the legal curriculum: Integration into the practice - Timothy Casey (Universitat Politècnica de València, 2014)
Legal education in the United States is at a crisis point. Simultaneously confronting scathing critiques and mounting market forces, legal education must change to survive. Experiential education offers the hope of increasing the relevance of legal education to the practice of law, and many law schools have adopted new programs where students learn through experience. This article provides an overview of legal education and describes the rise of experiential legal education. The article concludes with a description of an innovative program that integrates the practice in the joint enterprise of educating tomorrow's lawyers.